Atividades de prática deliberada e jogo deliberado na formação esportiva de atletas de elite do voleibol: diferenças entre os sexos - Collet, C.; Vieira do Nascimento, J.; Folle, A.; Ibanez, S. J. (Revista Ciencia del Deporte, 2017)
The aim of the present study was to verify the associations between the activities of deliberate practice and deliberate play performed during the sports development with the sex of the elite athletes of Brazilian volleyball. The participants were 102 volleyball athletes from the national men's and women's national teams, from the younger categories and adult selections. The athletes answered a questionnaire about their sports formation and the data were analyzed from the Chi-square test. The results showed significant associations between the types of deliberate practice activities and the sexes, in which the girls specialized in volleyball earlier, while boys engaged in more diversified activities. In contrast, deliberate play activities were similar in all the stages of sports development. Thus, it is concluded that the differences between the sexes should be taken into account in the process of sports training, although they should not constitute a limiting factor of opportunities for both sexes.